A case of an 11-year-old boy with paediatric inflammatory multisystem syndrome associated with coronavirus disease, haemophagocytic lymphohistiocytosis, and systemic juvenile idiopathic arthritis - Błaszczyk, Ewa; Firek-Pędras, Małgorzata; Berdej-Szczot, Elżbieta; Mizia-Malarz, Agnieszka; Gruenpeter, Anna; Lachór-Motyka, Iwona; Więcek, Sabina; Gawlik-Starzyk, Aneta (Pediatria Polska - Polish Journal of Paediatrics, 2024)
After the announcement of the coronavirus disease 2019 (COVID-19) pandemic, a new disease connected with SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) infection was described: paediatric multisystem inflammatory syndrome associated with coronavirus disease (PIMS). PIMS is an acute and potentially dangerous inflammatory syndrome that may lead to cardiac complications. It requires differential diagnosis with Kawasaki disease. Some patients with PIMS can develop macrophage activation syndrome (MAS), which until now has occurred most commonly with systemic-onset juvenile idiopathic arthritis (JIA) and is closely related to haemophagocytic lymphohistiocytosis (HLH). In this article we present a case report of a patient with diagnosed PIMS, including PIMS with MAS, and with later diagnosis of HLH and JIA.